The direct catalytic enantioselective synthesis of protected aryl beta-hydroxy-alpha-amino acids. - Willis, M; Cutting, G; Piccio, V; Durbin, M; John, M (2005)
The combination of three reagents-a tridentate pybox ligand (pybox = pyridine bis(oxazoline)), magnesium perchlorate, and Hünig base (iPr 2EtN)-allows the catalytic generation of a chiral glycine enolate from 1 that undergoes highly enantioselective addition to a range of aryl aldehydes 2. The protected aryl β-hydroxy-α-amino acid products obtained include a protected version of one of the aryl serine units present in the glycopeptide antibiotic vancomycin. © 2005 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.